ANALISIS KEBIJAKAN KURIKULUM PENDIDIKAN INDONESIA DARI MASA KE MASA (DALAM PERSPEKTIF PENDIDIKAN ISLAM DAN PENDIDIKAN NASIONAL) - Ulinniam; Sarwo Edy; Sumarta (Sinau : Jurnal Ilmu Pendidikan dan Humaniora, 2023)
In an education system, the curriculum is dynamic and constantly changing and developing to support the developments and challenges of the times. However, changes and developments must be carried out in a systematic and directed manner, not just changes. The history of the program in Indonesia has come a long way, history records changes after 1947, 1952, 1964, 1975, 1984, 1994, 2004, 2006 and the most recent program in 2013. Therefore, in order not to fall into the same genre, the government must make every effort possible so that curriculum implementers in the field, especially teaching staff, can understand curriculum ideas adequately and correctly. The curriculum as a new reform strategy is more important than the teacher as merely implementing the curriculum. On the other hand, changes are needed in the formulation of the curriculum, the curriculum must be formulated holistically, taking into account the philosophical, educational, sociological, social, cultural, technical and political foundations as the basis of the curriculum, and taking into account the real conditions of society and the world of education.